Land Subsidence in Dukuh Tambak Gojoyo, Wedung, Demak and Its Mitigation - Cahyo Wulandari; Meidita Farah Widodo; Gunawan Tri Santosa; Dwi Rahman Putra (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Tambak Gojoyo Hamlet, located on the northern coast of Demak, faces a serious issue of land subsidence caused by excessive groundwater extraction through deep wells equipped with high-capacity pumps. This phenomenon is exacerbated by the lack of mangrove vegetation in coastal areas, which accelerates seawater intrusion, tidal flooding, and the decline of groundwater quality. This study aims to map the potential areas affected by subsidence, calculate the rate of land subsidence, and propose mitigation strategies based on conservation and simple technology. This activity is part of a community service program conducted through the KKN-PPM UGM Unit Wedung 2025. The methods employed include field surveys, household interviews, groundwater well measurements, and quantitative analysis of well depth, pump type, and water consumption. The results indicate that the risk radius of subsidence ranges between 70–150 meters from well points, with an annual land subsidence rate of 0.3121 m/year in coastal areas and 0.0084 m/year in areas located farther inland. Proposed conservation measures include mangrove rehabilitation to stabilize the groundwater table and the optimization of surface water utilization through a simple evaporation-based desalination system, supported by the potential use of existing rubber dam infrastructure for water distribution. Community education programs successfully improved awareness of subsidence risks and conservation measures, as demonstrated by the significant increase in posttest scores (8,1) compared to pretest results (3,5). These findings emphasize the importance of combining technical solutions with community participation to effectively mitigate subsidence and ensure the sustainability of coastal environments.Keywords: land subsidence; groundwater; mangrove; desalination; community service